MEDIA EDUCATION AS A FACTOR IN THE DEVELOPMENT OF STUDENTS' CRITICAL THINKING IN THE LESSONS OF FOREIGN LITERATURE IN SENIOR CLASSES - Rozman, Iryna; Kravchenko, Lesya (Mountain School of Ukrainian Carpaty, 2023)
The article examines the process of implementing media education for the development of students' critical thinking in foreign literature lessons in high school. It is noted that media education helps students develop critical thinking skills about the information they consume in the media, helps them analyze, evaluate and perceive various media formats, making them less vulnerable to manipulation and inaccurate information. The article notes that media education is a component of modern education, which is aimed at developing students' media literacy and covers various aspects of media work. It is emphasized that the appropriate use of media education, the ability to analyze, understand, critically perceive and use various media formats will contribute to the development of students' critical thinking. It has been proven that the use of informational teaching aids in foreign literature lessons will contribute to the use of multimedia resources to improve the understanding of texts, create content for literary analysis, and more actively study the material. Internet resources are offered that will help effectively plan lessons and extracurricular activities in educational institutions. It is emphasized that in high school foreign literature classes, it is appropriate to use a variety of media sources: films, videos, websites, etc., related to the works studied and offered for additional reading. We emphasized that media literacy consists in the ability to critically evaluate these sources and their correspondence to the original text. A comparison of the theoretical concepts of media education of research scientists is carried out, which proves the need to explore not only the theoretical possibilities of media resources, but also to emphasize the practical importance of media literacy, not forgetting the problems of media violence, the consequences of its influence on a minor audience. It was found that in the process of media education, the student's information competence is purposefully formed and developed. This involves the ability to work with various information, create and interpret media text, and possess skills.